2001
DOI: 10.4141/a00-055
|View full text |Cite
|
Sign up to set email alerts
|

The role of angiotensin II in the central regulation of feed intake in sheep

Abstract: [215][216][217][218][219][220][221]. The objective was to determine the role of Angiotensin II (ANG) in the central regulation of feed intake by ruminants. As a control treatment, artificial cerebrospinal fluid (CSF) was given (over a period of 98.5 h) as a continuous intracerebroventricular (ICV) infusion (0.2 mL h -1 ) into the lateral ventricle of ewes (n = 5). Approximately 9 d later, the infusion was repeated with the same ewes, but the CSF contained ANG (25 µg mL -1 ). The ewes were fed dried alfalfa cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…From these results, it is thought that to maintain a homeostasis in water and Na content of body fluid, the renin–angiotensin system was activated and vasopressin was released in P sheep (Ramsay & Ganong 1986). The intravenously injected vasopressin or ICV infused angiotensin II (AngII) decreased feed intake in sheep (Meyer et al 1989; Sunagawa et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results, it is thought that to maintain a homeostasis in water and Na content of body fluid, the renin–angiotensin system was activated and vasopressin was released in P sheep (Ramsay & Ganong 1986). The intravenously injected vasopressin or ICV infused angiotensin II (AngII) decreased feed intake in sheep (Meyer et al 1989; Sunagawa et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore thought that vasopressin and AngII depressed feeding in P sheep. In NP sheep with continuous access to water and 0.5 mol/L NaCl solution, ICV infused AngII caused an increase in salt intake (Sunagawa et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in feed intake during intracerebroventricular infusion of angiotensin II are caused by the production of thirst sensations in the brains of ewes leading to excessive water intake and ruminal distension (Sunagawa et al 2001). It was also reported that intraperitoneal injections of vasopressin decrease feed intake in goats (Meyer et al 1989).…”
Section: Plasma Glucose Concentrationmentioning
confidence: 99%
“…Parotid saliva secretion volumes in ruminants contribute 50 to 70% of the total mixed saliva secretion volumes (Tsuda et al 1994). Up to this point, Sunagawa et al (2001Sunagawa et al ( , 2005Sunagawa et al ( , 2007b have intravenously infused animals continuously with hypo-osmotic and iso-osomotic artificial saliva beginning 1 h prior to the commencement of feeding. Plasma osmolarities during infusion were comparatively low or equal to non-infusion values.…”
Section: Plasma Glucose Concentrationmentioning
confidence: 99%
“…The intravenous infusion of ANG II reduced parotid saliva secretion in ewes ( McKinley et al, 1979 ). Sunagawa et al (2001) reported that brain ANG II reduced dry forage intake in sheep. These facts indicate that the marked suppression of dry forage intake during the first hour was caused by a feeding-induced hypovolemia while the suppression of saliva secretion was brought about by the loss of NaHCO 3 from the blood due to increased saliva secretion during the initial stages of dry forage feeding.…”
Section: Introductionmentioning
confidence: 99%